PROFESSIONALS’ OPINIONS ON MULTIDIMENSIONAL APPROACH TO EARLY INTERVENTION FOR CHILDREN WITH ASD - Kardara, Eleni Anna; Andromachi, Nanou (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Early intervention methods for children with Autism Spectrum Disorders, increasingly turn to multidimensional approaches with a parallel focus on interprofessional collaboration in order the interventions to be effective. Multidimensional approaches efficiently support the complex system of family interaction and function affecting positively the child’s development. Early and efficient interventions are widely recognized to lead to long-term positive socio-cognitive results for children with Autism Spectrum Disorders and their families. The purpose of this research is to delve into professionals’, special educators ’and therapists’, opinions on their collaboration with parents and other professionals as they apply early intervention programs to children with ASD. Semi-structured interviews of 15 professionals, experts on early intervention in children with ASD, from different regions of Greece, were analyzed using qualitative research methods. Part of the data analysis that presented in this paper demonstrates clearly that the professionals’ and special educators’ opinions emphasize the need for multidimensional approaches. The analysis also highlights the obstacles that restrict collaboration with parents and other professionals. The material resources of state support have also been suggested as factors that interact with family resources that affect the child’s developmental characteristics.